Pengaruh Motivasi Dan Religiusitas Terhadap Kinerja Karyawan Pada Unit Usaha Syariah Bank 9 Jambi Kota Jambi - Fadhlidzil Ikram; Lucky Enggrani Fitri; Ary Dean Amri (Journal of Islamic Banking, 2025)
This study aims to analyze the impact of motivation and religiosity on employee performance at the Unit Usaha Syariah Bank 9 Jambi. This research employs a quantitative approach with a survey method. Data was collected using a questionnaire distributed to 34 employees of the bank, measured using a Likert scale. The data analysis technique used is multiple linear regression. The results show that motivation has a significant positive effect on employee performance, with a regression coefficient of 0.364 and a significance level of 0.000. Similarly, religiosity has a significant positive effect on employee performance, with a regression coefficient of 0.481 and a significance level of 0.002. Simultaneously, both motivation and religiosity have a significant effect on employee performance, with an F-value of 18.431 (p < 0.05). These findings suggest that both motivation and religiosity play a crucial role in enhancing employee performance in the Islamic banking sector. It is recommended that Unit Usaha Syariah Bank 9 Jambi continue to consider motivation and religiosity in its managerial policies to improve employee performance. This research also opens opportunities for future studies to examine other factors influencing employee performance.